Recent developments in catalytic amide bond formation. Issue 6 (16th November 2020) - Todorovic, Mihajlo; Perrin, David M.
Abstract: Amide bond forming reactions are critical for both polypeptide synthesis and medicinal chemistry. Most current approaches for amidation employ stoichiometric activating agents, but such methods are neither atom economical nor synthetically elegant. Catalytic approaches for amidation are potentially green and more ideal substitutes for current standard methods and thus are the subject of this review. Such methods face significant thermodynamic and kinetic barriers and have, as a result, historically conceded the use of elevated temperatures and dehydrating agents or lacked broad and relevant substrate scopes from the perspective of peptide chemistry. Recent advancements in methods for both direct amidation (the coupling of a carboxylic acid and an amine) and indirect amidation (the coupling of other partners resulting in an amide bond) based on aryl boronic acids, transition metals and organocatalysis for the former and ester amidation and redox‐coupled amidation for the later, address these previous shortcomings and are examined therein. Abstract :